Antihypertensive Activity in High Salt-Induced Hypertensive Rats and LC-MS/MS-Based Phytochemical Profiling of Melia azedarach L. (Meliaceae) Leaves. - Saeed, Anam; Bashir, Kashif; Shah, Abdul Jabbar; Qayyum, Rahila; Khan, Taous (BioMed Research International, 2022)
Melia azedarach L. leaves have been traditionally used but not scientifically evaluated for antihypertensive activity. The focus of the present work was to carry out the detailed phytochemical profiling and antihypertensive potential of methanolic extract and subsequent fractions of this plant. The tandem mass spectrometry-based phytochemical profiling of M. azedarach extract (Ma.Cr) and fractions was determined in negative ionization mode while molecular networking was executed using the Global Natural Product Social (GNPS) molecular networking platform. This study resulted in the identification of 29 compounds including flavonoid O-glycosides, simple flavonoids, triterpenoidal saponins, and cardenolides as the major constituents. Ma.Cr at the concentration of 300 mg/kg resulted in a fall in blood pressure (BP), i.e., 81.44 ± 2.1 mmHg in high salt-induced hypertensive rats in vivo, in comparison to normotensive group, i.e., 65.36 ± 1.8 mmHg at the same dose. A decrease in blood pressure was observed in anaesthetized normotensive and hypertensive rats treated with extract and various fractions of M. azedarach. A reasonable activity was observed for all fractions except the aqueous fraction. The highest efficacy was shown by the ethyl acetate fraction, i.e., 77.06 ± 3.77 mmHg in normotensive and 88.96 ± 1.3 mmHg in hypertensive anaesthetized rats. Ma.Cr and fractions showed comparatively better efficacy towards hypertensive rats as compared to rats with normal blood pressure. Blood pressure-lowering effects did not change upon prior incubation with atropine. In vitro testing of Ma.Cr and polarity-based fractions resulted in L-NAME sensitive, endothelium-dependent vasodilator effects on aortic tissues. Pretreatment of aorta preparations with Ma.Cr and its fractions also blocked K+-induced precontractions indicating Ca2+ channel blocking activity comparable to verapamil. The extract and polarity-based fractions did not reveal a vasoconstrictor response in spontaneously beating isolated rat aorta. Ma.Cr and fractions when used in atrial preparations resulted in negative inotropic and chronotropic effects. These effects in atrial preparations did not change in the presence of atropine. These effects of extract and fractions explained the antihypertensive potential of M. azedarach and thus provided a scientific basis for its ethnopharmacological use in the treatment of hypertension. Among the constituents observed, flavonoids and flavonoid O-glycosides were previously reported for antihypertensive potential.